Hyperglycemia causes differential change in macrophage population in the lacrimal gland, conjunctiva and cornea - Alfuraih, Saleh; Tran, Amy; Kim, Lois; Ansari, Rais; Sharma, Ajay (Frontiers in Immunology, 2024)
BackgroundDue to its location, the ocular surface is exposed to environmental microbes. Innate immune cells including macrophages are first line defense against infections. In vitro exposure to high glucose as well as diabetes-associated hyperglycemia has been shown to affect innate immune cell function and population. The present study was designed to examine the effect of diabetes-associated hyperglycemia on the lacrimal gland, conjunctiva and cornea macrophage population, phenotypic changes and cytokines/chemokines.MethodsMouse model of Streptozotocin-induced diabetes was used to induce hyperglycemia. Immunostaining for CD11b and F4/80 was performed to stain macrophages in whole mount cornea, conjunctiva and 50 µm lacrimal gland sections. Flowcytometry was performed on single cell suspension to identify macrophage phenotypes and activation using CD11b, F4/80, CD80, CD206 and MHCII staining. Real time PCR was performed to quantify gene expression for macrophage-associated cytokines (IL-1β, TNF-α, IFN-γ) and chemokine (CCL2).ResultsOur data demonstrates the diabetes-associated hyperglycemia caused a rapid onset and significant decrease in macrophage population in lacrimal gland, conjunctiva and cornea. The onset of this noted decrease was as early as 7 days after hyperglycemia in lacrimal gland and conjunctiva followed by a notable increase towards recovery only in conjunctiva but not in the lacrimal gland. The cornea tissue showed a steady decline up to the tested time point of 28 days. Further, hyperglycemia did not cause any notable changes in macrophage phenotypes, their activation status or the expression of IL-1β, TNF-α, IFN-γ, CCL2 except in the cornea where an increase in the cytokine levels was noted after 7 days of hyperglycemiaConclusionOur data shows that diabetes-associated hyperglycemia can cause a significant decrease in microphage population with changing their plasticity or activation status in lacrimal gland, conjunctiva and cornea but the kinetics of decrease and recovery show differential pattern specific for each tissue.